Analisis Pemanfaatan Sistem Cashless Society Dalam Meningkatkan Loyalitas Pelancong Di Pasar Tradisional Kota Bukittinggi - Trimaulina, Yona; Kasmira, Arini; Matondang, Rio Ahmad Alfikri; Tamimi, Muhammad Khoalid at; Maulana, Yoga (Musamus Journal of Public Administration, 2024)
Technological developments in the 4.0 era are increasingly expanding to human payment systems in the buying and selling process, with the existence of a non-cash payment system (cashless society) where the system can also be present in traditional markets, especially in Bukittinggi City. The implementation of a cashless society system in traditional markets has enormous potential to increase traveler loyalty, help improve the local economy, especially MSMEs, and can provide significant growth opportunities in the growth of Bukittinggi City. The data collection technique in this research uses 2 techniques, namely primary, namely observation at the Bukittinggi Traditional Market and direct interviews with sellers and tourists, and the second technique is secondary by conducting a literature survey of books, journals, theses and policy documents related to the cashless society. and traveler loyalty. The data analysis technique used is a descriptive analysis technique, namely drawing conclusions from specific statements or facts into specific problems and making general conclusions in accordance with the available theories. The results of the research reveal that there are several factors that make the implementation of cashless not work as expected, namely a lack of counseling and education to all parties, traders who are not ready to implement cashless, limited ownership of equipment, and money that takes a long time to enter the seller's bank if they use it QRIS